Discursive Strategies for the Social Construction in the Post-Conflict Era (2015-2017) (2019)
The objective is to analyze the linguistic and rhetorical resources used in the discursive construction about the social actors of the post-conflict, through the study of nine editorials of the newspaper El Espectador, between the years 2015-2017. The research is woven from the perspective of Critical Discourse Analysis (CDA), in order to make a theoretical formulation about journalistic discursive manifestations and a critical reflection on the social realities of journalistic language. The methodology was developed in two stages: an exploratory-descriptive and an analytical one. In the first, a compilation of the editorials under study is made to be submitted to the qualitative analysis program NVivo 11, reporting significant elements such as the frequency of words, co-texts, and the cloud mark and the conglomerates. The second involved the realization of a linguistic analysis to interpret the strategies of legitimation, naturalization and concealment used to discursively construct the social actors of the post-conflict.